Endothelial Dysfunction in Pregnancy Metabolic Disorders - Cabello-Verrugio, C (Elsevier B.V., 2020)
In recent years, the vascular endothelium has gained attention as a key player in the initiation and development of pregnancy disorders. Endothelium acts as an endocrine organ that preserves the homeostatic balance by responding to changes in metabolic status. However, in metabolic disorders, endothelial cells adopt a dysfunctional function, losing their normal responsiveness. During pregnancy, several metabolic changes occur, in which endothelial function decisively participates. Similarly, when pregnancy metabolic disorders occur, endothelial dysfunction plays a key role in pathogenesis. This review outlines the main findings regarding endothelial dysfunction in three main metabolic pathological conditions observed during pregnancy: gestational diabetes, hypertensive disorders, and obesity and hyperlipidemia. Organ, histological and cellular characteristics were thoroughly described. Also, we focused in discussing the underlying molecular mechanisms involved in the cellular signaling pathways that mediate responses in these pathological conditions. © 2019 Elsevier B.V.